Antitoxic Effects of Chicory Herb Extract Fractions in Rats with Toxic Hepatitis - I. A. Lupanova; O. L. Saybel; E. N. Kurmanova; E. V. Ferubko; I. A. Martynchik; P. G. Mizina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To evaluate the antitoxic activity of chicory herb extract fractions in rats with toxic hepatitis.Materials and methods. There were 64 male rats were divided into groups of 6 animals that received the whole chicory herb extract, its fractions, or the reference drug (RD) and 2 groups did not receive any drug. The Silimar substance (a dry purified extract obtained from the fruits of milk thistle [Silybum marianum]) was chosen as RD. Animals from one of the groups that did not receive the drug (control group) and the groups that received drugs were injected with CCl4 to simulate toxic liver damage. The last group of animals received neither drugs nor CCl4 (intact animals). The changes in the activity of biotransformation enzymes (cytochrome P450 [cytР450] and glutathione transferase [GT]) in hepatocytes and serum liver enzymes (AST, ALT and AP) were assessed.Results. There was a decrease in cytР450 and GT activity in the liver microsomes of control rats (having CCl4 hepatitis without treatment) compared with intact animals. These parameters were more in the animals that were administrated with chicory herb extract, its fractions, and RD than in control animals. The administration of the whole extract, aqueous fraction, and RD led to an increase in the activity of cytP450 and GT enzymes almost to the level of the same indicators in intact animals. Pronounced grown in the activity of serum liver enzymes (ALT, AST and AP) were found after CCl4 injection. Administration of common chicory herb fractions before toxic liver damage caused a decrease in the grown of the activity of these enzymes. The greatest inhibitory effect on the grown of the activity of these liver enzymes had RD, aqueous and butanolic fractions of chicory herb. Despite a significant decrease in hyperfermentemia found in groups of animals treated with fractions of chicory herb, AST, ALT and AP activities did not reach the level that was in the intact animal group.Conclusion. The aqueous and butanolic fractions of the chicory herb extract had the highest antitoxic activity in experimental animal toxic liver injury.